Service-learning at CES Don Bosco: Good Practices - Sánchez-Huete, Juan Carlos; Marquès Donoso, Albert (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2021)
Service-learning is a methodology that has transformed the practical view of teaching and has shared with society the results of projects designed by students from different educational stages. this paper analyses the theoretical grounds of service-learning as a teaching methodology framed within the Ba competences at CES Don Bosco. hence different theoretical grounds will be addressed from a pedagogical, psychological and sociológica perspective. an implementation proposal aimed at the students of our university institution is presented here, thus showing two examples carried out in two courses, one from the Ba in Pedagogy and another from the Ba in Social education, so that they might become references for the implementation of service-learning in university contexts.